Correction: The novel anti-inflammatory activity of mcIRBP from Momordica charantia is associated with the improvement of diabetic nephropathy. Issue 3 (26th January 2022) - Liao, Pei-Yung; Lo, Hsin-Yi; Liu, I-Chen; Lo, Lun-Chien; Hsiang, Chien-Yun; Ho, Tin-Yun
Abstract : Correction for 'The novel anti-inflammatory activity of mcIRBP from Momordica charantia is associated with the improvement of diabetic nephropathy' by Pei-Yung Liao et al., Food Funct., 2022, DOI: ; 10.1039/d1fo03620c .